Requirements engineering: Foundation for Software Quality: 23rd International Working Conference, REFSQ 2017, Essen, Germany, February 27 – March 2, 2017, proceedings - Grünbacher, Paul; Perini, Anna (Lecture notes in computer science, 2017)
This book constitutes the proceedings of the 23rd International Working Conference on Requirements Engineering - Foundation for Software Quality, REFSQ 2017, held in Essen, Germany, in February/March 2017. The 16 full papers and 10 short papers presented in this volume were carefully reviewed and selected from 77 submissions. The papers were organized in topical sections named: use case models; ecosystems and innovation; human factors in requirements engineering; goal-orientation in requirements engineering; communication and collaboration; process and tool integration; visualization and representation of requirements; agile requirements engineering; natural language processing, information retrieval and machine learning traceability; quality of natural language requirements; research methodology in requirements engineering
Keywords: Konferenzschrift; Qualitätssicherung; Softwareprodukt; Requirements engineering